CS Dietary software system to support the entry, management, and processing of quantitative 24-hour dietary recall survey data - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Software was developed by HarvestPlus and SerPro SA. In 2020, it was made freely available for download through Intake’s online resource library. Intake provides technical assistance to support national or large-scale dietary surveys around the world.